On the existence and uniqueness of a solution of a linear stochastic differential equation with respect to a logarithmic process - Pilipenko, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study the problem of existence and uniqueness of a solution of a linear stochastic differential equation with respect to a logarithmic process. For the conditional mathematical expectation of a solution, we obtain a partial differential equation.